Effect of Genetic Variations in Syntaxin-Binding Protein-5 and Syntaxin-2 on von Willebrand Factor Concentration and Cardiovascular Risk - van Loon, Janine E.; Leebeek, Frank W.G.; Deckers, Jaap W.; Dippel, Diederik W.J.; Poldermans, Don; Strachan, David P.; Tang, Weihong; OʼDonnell, Christopher J.; Smith, Nicholas L.; de Maat, Moniek P.M. (Circulation. Cardiovascular genetics, 2010)
BACKGROUND—Elevated von Willebrand factor (VWF) plasma levels are associated with an increased risk of cardiovascular disease. A meta-analysis of genomewide association studies on VWF identified novel candidate genes, that is, syntaxin-binding protein 5 (STXBP5) and syntaxin 2 (STX2), which are possibly involved in the secretion of VWF. We investigated whether VWF antigen levels (VWF:Ag), VWF collagen-binding activity (VWF:CB) and the risk of arterial thrombosis are affected by common genetic variations in these genes. METHODS AND RESULTS—In 463 young white subjects (men ≤45 years of age and women ≤55 years of age), who were included 1 to 3 months after a first event of arterial thrombosis, and 406 control subjects, we measured VWF:Ag and VWF:CB. Nine haplotype tagging single-nucleotide polymorphisms of STXBP5 and STX2 were selected and subsequently analyzed using linear regression with additive genetic models adjusted for age, sex, and ABO blood group. The minor alleles of rs9399599 and rs1039084 in STXBP5 were associated with lower VWF plasma levels and activity, whereas the minor allele of rs7978987 in STX2 was associated with higher VWF plasma levels and activity. The minor alleles of the single-nucleotide polymorphisms in STX2 were associated with a reduced risk of arterial thrombosis (rs1236odds ratio, 0.73 [95% confidence interval, 0.59, 0.89]; rs7978987odds ratio, 0.81 [95% confidence interval, 0.65, 1.00]; rs11061158odds ratio, 0.69 [95% confidence interval, 0.55, 0.88]). CONCLUSIONS—Genetic variability in STXBP5 and STX2 affects both VWF concentration and activity in young individuals with premature arterial thrombosis. Furthermore, in our study, genetic variability in STX2 is associated with the risk of arterial thrombosis. However, at this point, the underlying mechanism remains unclear.